EXTENT OF HEMODIALYSIS NURSES’ PRESENCE AS PERCEIVED BY PATIENTS - Ma. Almira Pliego Nebres; Clarence Bien Ladion Nebres; Bienvisa Ladion Nebres (Belitung Raya Foundation, Indonesia, 2020)
Background: Nursing presence is an essential nurse caring behavior of being with the patient. This is particularly true for those with chronic renal disease and who regularly undergo maintenance hemodialysis treatment in the hospital setting. When nursing presence is perceived by patients in a nurse-patient relationship, it is more likely to result in enhanced satisfaction with the quality of nursing care. Thus, it is important for hemodialysis nurses to be aware of the relevance of nurse-patient interactions in planned care considering that these interactions are integral to the extent to which nursing presence is experienced and perceived by patients.Objective: This study aims to determine the hemodialysis nurses’ extent of nursing presence as perceived by patients undergoing hemodialysis treatment in two hospitals in Iligan City, Philippines.Methods: Utilizing the descriptive research design, the study was conducted in two hospitals in Iligan City, Philippines. A total of 121 hemodialysis patients were purposely selected to determine their perception as to the extent of hemodialysis nurse’s nursing presence utilizing the 25-item Presence of Nursing Scale (PONS) instrument. Descriptive statistics were used for data analysis.Result: The overall rating by the hemodialysis patients in both hospitals was “always